Evaluation of maize genotypes under mixed cropping lay legume system with climbing bean (Phasseolus vulgaris) at high altitude* - BANDYOPADHYAY, B B (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during rainy (kharin seasons of 2003 and 2004 on variability in yield and other traits of 7 maize (Zea r zays L.) genotypes on monoculture and associated with bean at high altitude on different conditions of soils. Two locally collected climbing bean cultivars that differed with respect to short and broad leaf character and nodulation capacity were considered for this investigation. Bean cultivars were used in rotation before sowing the maize, in previous year, on experimental plots. Observation was recorded on prolificacy index, 100-seed weight, fodder and grain yield. Components of variance and correlation analysis revealed that the cultivation of maize crop was found suitable in association with short leaf bean on a condition of soil amended by broad leaf bean cultivars. Non-additive effect of gene exploited for selection.